2015
DOI: 10.1002/casp.2263
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years Post‐genocide: The Creation of Mental Health Competence among Rwandan Survivors Through Community‐based Healing Workshops

Abstract: Twenty years after the genocide, many Rwandans still suffer from the psychological wounds of the past. The country's mental health agenda is based on individualised and psychiatric approaches that help some but cannot be provided on a large scale. Further, many reconciliation initiatives have been based on public testimonies, which have been shown to be potentially re‐traumatising, leading to calls for small‐scale community‐based approaches to healing, which constitute a middle way between individualised and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
(26 reference statements)
2
7
0
Order By: Relevance
“…Thus, women were able to expand and retain their local social networks, learn coping skills from others, and not feel alone. This is consistent with a study in Rwanda that used community-based approaches for establishing safe social spaces and income generation (Mahr & Campbell, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, women were able to expand and retain their local social networks, learn coping skills from others, and not feel alone. This is consistent with a study in Rwanda that used community-based approaches for establishing safe social spaces and income generation (Mahr & Campbell, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Sexual violence has been widely associated with risk for depression and anxiety, suicidal ideation, physical injury, HIV infection, other sexually transmitted infections, gastrointestinal disorders, genito-anal trauma, and pregnancy (Jina & Thomas, 2013). Without access to supportive services to encourage recovery and reintegration, survivors may be at increased risk for continued emotional, physical, and economic suffering (Mahr & Campbell, 2015; Spangaro, Adogu, Zwi, Ranmuthugala, & Davies, 2015; Stark, Landis, Thomson, & Potts, 2016). In this article, we focus on conflict-related sexual violence according to the United Nations definition (United Nations Secretary-General, 2015): “Rape, sexual slavery, forced prostitution, forced pregnancy, enforced sterilization and other forms of sexual violence of comparable gravity perpetrated against women, men, girls or boys that is linked, directly or indirectly to a conflict.”…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the positive impact of this type of support for IPV survivors has been shown to be sustainable over longer periods of time (Santos et al 2017). Another major strength of the women's safe spaces was the opportunity for livelihoods skills training and income generation, which is consistent with other research in Rwanda emphasizing the value of safe spaces combined with income generation activities (Mahr and Campbell 2015). Focus groups with Rwandan GBV survivors that were members of a support group found that these groups strengthened safety, stability, trust and interpersonal connections.…”
Section: Discussionsupporting
confidence: 80%
“…Mannell et al (2018) found that common responses of the Rwandan GBV committees include encouraging women to marry or remain with abusive partners, and prioritizing physical over emotional forms of violence, indicating limited understanding of the mental health consequences of IPV. Access to psychological care is critical for GBV survivors, as those who receive positive and supportive responses are less likely to experience post-traumatic stress (Edwards et al 2015;Mannell et al 2018), or remain at heightened risk for ongoing emotional, physical and economic suffering (Mahr and Campbell 2015). There is a particular gap in understanding Rwandan men's access to mental health support and trauma care, which has implications for both GBV prevention and response.…”
Section: Rwandan Contextmentioning
confidence: 99%
“…Wider and denser social networks can facilitate recovery by expediting access to resources and guidance, engendering community mobilization, and raising the cost of community exit (Landau and Saul, 2004; Aldrich, 2011). In relation to Rwandan post-genocide recovery, the need to promote social capital has been recognized (Scholte and Ager, 2014; Verduin et al, 2014; Mahr and Campbell, 2016). The violence of mass conflict and genocide destroys social ties, extirpates mutual trust, and shatters social cohesion.…”
Section: Literature Reviewmentioning
confidence: 99%